Market Opportunity and Consumer Preferences Analysis for Sawo (Manilkara zapota L.) Product Diversification as a Local Agribusiness in Angkola Muaratais District - Abdul Rahman Suleman; Siti Hardianti Wahyuni; Muhammad Noor Hasan Siregar (Majalah Ilmiah Bijak, 2025)
This study aims to identify the potential for diversification of products from sapodilla fruit (Manilkara zapota L) that need optimally utilized and have high market opportunities in Angkola Muaratais District. Using a descriptive qualitative approach supported by quantitative analysis, this research involved 42 respondents: farmers, workers, SME entrepreneurs, and consumers. Data were collected through in-depth interviews, structured questionnaires, and participatory observation, followed by mixed-method analysis, including product evaluation matrix and market feasibility analysis. Results show three main potential products with significant development opportunities. Premium sapodilla syrup shows the highest potential (score 4.24/5.0), followed by variant sapodilla chips (4.08/5.0) and natural sapodilla jam (3.92/5.0). Market segmentation analysis identifies three main consumer segments: health-conscious (35%), convenience seekers (40%), and traditional value seekers (25%). Digital market penetration projections indicate significant growth potential, reaching 85% through social media and e-commerce channels within six months. Product evaluation reveals that premium sapodilla syrup excels in raw material availability (4.5/5.0) and shelf life (4.5/5.0), while variant sapodilla chips show highest market interest (4.5/5.0) and value addition potential (4.5/5.0). The study indicates substantial market potential with a Total Available Market of 150,000 consumers and a Serviceable Obtainable Market of 15,000 consumers, projecting 15-20% annual market growth. The findings contribute to understanding critical factors in local resource-based product development and support the Green Economy theory regarding sustainable value addition in local economic development. This research provides practical implications for product development strategies and policy recommendations for supporting the sapodilla processing industry at the regional level.